Alkali Metal Complexes: Homo-Binuclear Complexes of Alkali Metal Salts of Quinizarin with Some Oxygen Donor Ligands - Prakash, Dharma; Chandra, R.; Prasad, N.K.; Gupta, O.P. (Asian Journal of Chemistry, 2010)
A series of novel homo-binuclear complexes of the general formula M2L ·nHL´ (where M = Li, Na and K; L = quinizarin and HL´ = acetylacetone, benzoylacetone, saclicylaldehyde, o-hydroxy acetophenone, o-hydroxynaphthaldehyde, ethyl acetoacetate and ethyl malonate; and n = 2 or 4) have been synthesised and characterised on the basis of chemical analysis, conductance and infrared spectral studies. IR spectral data indicate the presence of hydrogen bonding in the complexes, which may be one of the essential features for the stability of these complexes. Low value of the molecular conductivity suggests the covalent nature of bonds in these complexes.